Current challenges and future directions of ATMPs in regenerative medicine - Fatemeh Abbasi Kakroodi; Elaheh Khodadoust; Marzieh Alizadeh; Reyhaneh Sadat Hayaei Tehrani; Pedram Asadi Sarabi; Mohammad Rahmanian; Massoud Vosough (Regenerative Therapy)
Advanced therapy medicinal products (ATMPs) represent a groundbreaking category of medications that utilize biological-based products to treat or replace damaged organs. It offers potential solutions for complex diseases through gene therapy, somatic cell therapy, tissue engineering, and combined therapies. Although ATMPs have offered significant improvement for a variety of severe illnesses, their progressive development is faced with numerous challenges. Some of these challenges are current complexities in their manufacturing, such as scaling up, scaling out, product efficacy, packaging, storage, stability, and logistic concerns. Other challenges include manufacturing, efficacy, and scaling up of ATMPs, as well as establishing Good Manufacturing Practice (GMP)-compliant processes that align with product specifications derived from non-clinical studies conducted under Good Laboratory Practice (GLP). Additionally, safety concerns such as tumorigenesis are potential. Regulatory and ethical concerns, along with the need for standardization and clear clinical guidelines, are also critical obstacles. To address these challenges, novel technologies such as organoids, artificial intelligence, dynamic culture systems, and biobanking are being explored, providing new opportunities to enhance the consistency, scalability, and precision of ATMP production. Development in artificial intelligence (AI) technology helped scientists to address monitoring concerns, automation, and data management. Introducing advanced guidelines in biobanking helps researchers to overcome the storage and stability concerns. Organoid technology holds a significant promise in overcoming the challenges associated with preclinical and modeling of ATMPs by providing more accurate models for diseases, drug screening, and personalized medicine. This article reviews the current challenges in ATMP manufacturing and application, highlights the advancements in technology that are paving the way for improved therapeutic strategies, and offers future perspectives on overcoming these barriers.